The role of circular economy in peripheral countries: a multiple helix approach - Julião, Jorge (2017)
Over the past decades, more attention has been given worldwide to sustainability issues, like the scarcity of natural resources, waste management, and climate changes. The circular Economy has been assumed as a strategy to overcome these issues, since it implies the adoption of clean production, reuse of materials, use of renewable energies, waste recycling, among others. In recognition of this, several countries, like China, Japan, German, and Netherlands, have implemented legislation in favor of circular economy, whence successful experiences were obtained. An important learned lesson emphasizes the participation of all actors (governments, regional authorities, business and non-governmental organizations) in the transaction towards a Circular Economy strategy. The purpose of this chapter is to use a Multiple Helix approach to analyze and discuss the challenges and opportunities towards a Circular Economy in peripheral countries, identifying the implications of fostering sustainable economic growth and enhancing local competitiveness by means of an integrated approach.